Improved Smallholder Dairy Farming in Uganda through Technological Change - Mbowa, Swaibu; Shinyekwa, Isaac; Mayanja Lwanga, Musa (Economic Policy Research Centre (EPRC), 2012)
The dairy sector in Uganda has been transformed into a more competitive and dynamic sector. Supply-side factors have enabled expansion in milk production. Between 2005 and 2009 –milk production (estimated at 1.5 billion litres in 2010) has been partly an outcome of a 20 percent increase in the number of households engaged in dairy farming, and an increase (21 percent) in the proportion of crossbred dairy cows in the national herd (estimated to be 11 million cattle). At farm level concerted efforts have been directed towards technological change – transforming the farming system from predominantly extensive grazing local breeds to more intensive rearing of fewer but improved breeds. The lack of consistent long-term support to the breeding programs negatively affect numbers of dairy cattle stocks especially in Northern Uganda. Furthermore, the perpetually low farm gate milk prices could deter the optimal uptake of required dairy farm husbandry practices in the milk surplus Western region.